Art Music by Caribbean Composers: Curacao - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Folk musical traditions of Curaçao include tambu (also known as “the Curaçao blues”) and tumba (Razak, 2005). Art music has long had a presence in Curaçao. Orchestras, concert societies, and art musical instruction have been in place since the early 19th century (Gansemans, 2008). Composed dance music, for localized versions of dances such as waltz, polkas and mazurkas, is particularly popular in Curaçao (Gansemans, 2008). “The most important of these is the Antillean waltz (also known as the Curaçaoan waltz), distinguished from its European relatives chiefly by its differently accented rhythmic patterns” (Bilby, 2013, para. 10)